Energy dependence of intermittency for charged hadrons in Au+Au collisions at RHIC - M.I. Abdulhamid; B.E. Aboona; J. Adam; L. Adamczyk; J.R. Adams; I. Aggarwal; M.M. Aggarwal; Z. Ahammed; D.M. Anderson; E.C. Aschenauer; S. Aslam; J. Atchison; et al. (Physics Letters B, 2023)
Density fluctuations near the QCD critical point can be probed via an intermittency analysis in relativistic heavy-ion collisions. We report the first measurement of intermittency in Au+Au collisions at sNN = 7.7-200 GeV measured by the STAR experiment at the Relativistic Heavy Ion Collider (RHIC). The scaled factorial moments of identified charged hadrons are analyzed at mid-rapidity and within the transverse momentum phase space. We observe a power-law behavior of scaled factorial moments in Au+Au collisions and a decrease in the extracted scaling exponent (ν) from peripheral to central collisions. The ν is consistent with a constant for different collisions energies in the mid-central (10-40%) collisions. Moreover, the ν in the 0-5% most central Au+Au collisions exhibits a non-monotonic energy dependence that reaches a minimum around sNN = 27 GeV. The physics implications on the QCD phase structure are discussed.